Incorporating Transformative Gender Equality and Social Inclusion in Climate Information Services for Agriculture and Food Security - Dinh, Dannie; Mapedza, Everisto D.; Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate information services (CIS) involve the production, translation, transfer, and use of climate knowledge and information in decision-making and policy and planning. CIS in agriculture can be a critical means to build resilience and maintain food security and livelihoods for those most at risk in the face of climate change and variability, such as smallholder farmers. However, unless women and other marginalized groups were deliberately involved during the planning and development of agricultural innovations and services, it is still possible for them to be excluded from these innovations and services meant to help them cope with climate risks and uncertainties.